The logic of Russian foreign policy: Analysis from the Theory of political realism - Fuentes Fernández, Carolina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Relations between the United States of America and today’s Russian Federation have been the subject of detailed academic studies over the years. These two great powers have played an important role in shaping the international system. The purpose of this article is to provide an analysis of Russia’s foreign policy - from the realist approach to international relations - which cannot be separated from a parallel study of the behaviour of the West in general, and the United States of America in particular.